HUBUNGAN KADAR HEMOGLOBIN PADA IBU HAMIL TRIMESTER III DENGAN BERAT BADAN LAHIR BAYI DI PUSKESMAS TILAMUTA KABUPATEN BOALEMO - Ani Retni; Asni Ayuba (-, 2021)
The research is done in Puskesmas Tilamuta, Boalemo District. The aim of the research is to find out whether there is a correlation between the hemoglobin rate on pregnant woman on third trimester with birth weights. The type of the research is correlation descriptive using retrospective study design. The sampling technique is total sampling with population on the last three months with total respondents of 43 people. The technique is analyzing the data used in this research is univariat analysis by using proportion and percentage and bivariat analysis with chi square statistic using SPSS Application. The result showed that there is correlation between the hemoglobin rate on pregnant woman on third trimester with birth weights (ρ value = 0,001 < α = 0,05).